The Role of Local Communities in Forest Management Based on Local Wisdom: A Qualitative Descriptive Review - Samsidar, Samsidar (Journal of Horizon, 2024)
Local communities have long functioned as the primary custodians of forests across the Indonesian archipelago and across Southeast Asia and the broader tropics, utilizing accumulated generations of ecological knowledge, customary law, and adaptive social institutions to govern forest resources in ways that modern science is only beginning to fully appreciate. This qualitative descriptive review synthesizes evidence from twenty-three studies—seventeen primary studies drawn from structured literature searches of Indonesian and Southeast Asian community forestry contexts and six foundational international references on traditional ecological knowledge and community-based natural resource governance. Using qualitative content analysis as the primary analytical framework, the review examines four interrelated dimensions of local community involvement in forest management: customary spatial zoning and prohibition systems; traditional ecological knowledge and land management practices; adat (customary) leadership institutions and social capital; and the ecological, socio-cultural, and economic outcomes associated with local wisdom-based forest governance. The synthesis reveals that communities employing complete and culturally embedded local wisdom systems—including sacred grove designations, seasonal harvesting restrictions, and adat sanctions—consistently achieve superior forest conservation outcomes compared to state-managed or externally directed alternatives